Universal Portable Unit for Hydro-vacuum Dispersion of Metallic Melts: Improvement of the Technological Process - Sakhvadze, David; Jandieri, Gigo; Saralidze, Besik; Sakhvadze, Giorgi; Kuparadze, Anzor; Sulaqvelidze, Nata (Physics and Chemistry of Solid State, 2024)
The development of the technology and techniques of dispersing metal alloys is important both from the point of view of improving the quality of powders, as well as increasing the volume of production and increasing the economic and ecological safety of the technosphere. Metal powder is an indispensable functional component for many modern branches of industry. Against the background of the growing demands for the production of metal powders, we have developed and optimized a new device for hydro-vacuum dispersion of melts, the essence of innovation and advantage of which lies in sucking and dispersing the melt in the direction opposite to the action of the force of gravity, under 150-200g gravity overload conditions, where the main work is performed by hydraulic rarefaction resulting from a sharp (on 162°) refraction of direction and rapid expansion of a high-pressure water annular flow, with the superimposition of spatial shock- pulsating waves generated in the outer shell of the formed cone-shaped vortex. The device is characterized by high production and low energy costs, while powders - by increased specific surface, improved purity and high activity.